Government loan guarantees, market liquidity, and lending standards - Toni Ahnert; Martin Kuncl (European Central Bank (ECB), 2022)
We study third-party loan guarantees in a model in which lenders can screen, learn loan quality over time and can sell loans before maturity when in need of liquidity. Loan guarantees improve market liquidity and reduce lending standards, with a positive overall welfare effect. Guarantees improve the average quality of non-guaranteed loans traded and thus the market liquidity of these loans due to both selection and commitment. Because of this positive pecuniary externality, guarantees are insufficient and should be subsidized. Our results contribute to a debate about reforming government-sponsored mortgage guarantees by Fannie Mae and Freddie Mac.
Keywords: G01; G21; G28; 330; Mortgage guarantees; adverse selection; market liquidity; pecuniaryexternality; Pigouvian subsidy; Government Sponsored Enterprises